2016
DOI: 10.1557/mrc.2016.2
|View full text |Cite
|
Sign up to set email alerts
|

Allamanda cathartica flower’s aqueous extract-mediated green synthesis of silver nanoparticles with excellent antioxidant and antibacterial potential for biomedical application

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Meanwhile, the Ag/Ag 2 O spectra revealed a common peak in all the samples (1:30 P/Ag, 1:40 P/Ag, 1:50 P/Ag) situated at 430 nm. This peak corresponds to the characteristic surface plasmon resonance absorption band of Ag/Ag 2 O [56,57]. To date, several methods have been reported for Ag NPs and Ag2O NP synthesis [64].…”
Section: Uv-visible Spectroscopy and Bandgapmentioning
confidence: 99%
“…Meanwhile, the Ag/Ag 2 O spectra revealed a common peak in all the samples (1:30 P/Ag, 1:40 P/Ag, 1:50 P/Ag) situated at 430 nm. This peak corresponds to the characteristic surface plasmon resonance absorption band of Ag/Ag 2 O [56,57]. To date, several methods have been reported for Ag NPs and Ag2O NP synthesis [64].…”
Section: Uv-visible Spectroscopy and Bandgapmentioning
confidence: 99%
“…Meanwhile the Ag/Ag2O spectra revealed on a common peak in all the samples (1/30, 1/40, 1/50) situated at 430 nm. This peak corresponds to the characteristic surface plasmon resonance absorption band of Ag/Ag2O [19][20][21] .…”
Section: 11uv-visible Spectroscopymentioning
confidence: 99%
“…The result of the study showed significant antioxidant and antibacterial activity hence stating the presence of bioactive compounds. Further, flower extracts of Couroupita guianensis, Allamanda cathartica ( Karunakaran et al, 2016 ) mediated Ag-NPs have shown potential antioxidant activities. Jamdade et al (2019) reported that the novel Cu-NPs fabricated from Gnidia glauca and Plumbago zeylanica used as a promising antidiabetic agent; and have demonstrated that these particles are considered as a potential candidate in antidiabetic nanomedicine preparation.…”
Section: Applicationsmentioning
confidence: 99%